(untitled) (Advancements in Homeopathic Research, 2023)
Chronic renal failure (CRF) is a progressive and irreversible deterioration of renal functions. Diabetes, hypertension, indiscriminate use of antibiotics and non-steroidal anti-inflammatory drugs (NSAIDs) are major contributory factors of chronic kidney disease (CKD) or end stage renal disease (ESRD). (1,2) In modern system, the role of medicinal treatment is very limited while haemo or peritoneal dialysis is cumbersome and expensive. Economic and legal issues limit the possibility of renal transplant and depends on the availability of donor.(3) On the other hand, homoeopathic treatment, if sought at an early stage, can help in maintaining or to some extent reviving renal functions by lowering serum creatinine thereby improving GFR. Gupta et. al. has done some work on the medicinal treatment of this difficult disease and have published the results.(4)